2011
DOI: 10.3892/or.2011.1182
|View full text |Cite
|
Sign up to set email alerts
|

Significance of epidermal growth factor receptor gene mutations in squamous cell lung carcinoma

Abstract: Abstract. Epidermal growth factor receptor (EGFR) gene mutations have been reported to be clinically significant in non-small cell lung cancer (NSCLC). However, because most previous studies focused only on adenocarcinomas, EGFR mutations in other histotypes are poorly investigated. We evaluated the frequency of EGFR gene mutations in squamous cell carcinoma (SCC) and its clinicopathological features. In total, 89 frozen tumor specimens that had been first diagnosed as SCCs, were examined for EGFR mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…Furthermore, our comparison the clinicopathological characteristics of SQCCs and the profiles of major known oncogenic mutations revealed that SQCCs arising in never-smokers distinctly differ from those in the more common smoking-related SQCCs. Oncogenic mutations, especially EGFR mutations, occurred considerably more frequently in the never-smokers, which is consistent with findings from an earlier study [18]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our comparison the clinicopathological characteristics of SQCCs and the profiles of major known oncogenic mutations revealed that SQCCs arising in never-smokers distinctly differ from those in the more common smoking-related SQCCs. Oncogenic mutations, especially EGFR mutations, occurred considerably more frequently in the never-smokers, which is consistent with findings from an earlier study [18]. …”
Section: Discussionsupporting
confidence: 92%
“…For lung ADCs, driver mutations to EGFR , KRAS , HER2 , BRAF and AKT1 have been well reported [6, 1315], and considerable progress has been made in their treatment [16]. However, whether lung SQCCs harbor these known driver mutations remains controversial [17, 18]. Lung SQCCs are strongly associated with tobacco exposure and are characterized by a high mutational burden with a mean somatic mutation rate of 8.1 mutations per megabase [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rekhtman et al screened 95 biomarker-verified SqCLC and reported that EGFR/KRAS mutations do not occur in pure SqCLC, occasional detection of these mutations in samples diagnosed as “SqCLC” is due to the diagnosis of adenosquamous carcinoma (AD-SQC) and adenocarcinoma [18]. However, another similar study by Miyamae et al revealed that EGFR mutations were present in 3.4% of 87 validated SqCLC specimens [20]. In our study, we found that the frequencies of EGFR and KRAS mutation were 3.2% and 4.5%, respectively, which were comparable with the previous reports of 3.4% [20] and 4% [22], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR mutation rate is about 50% among nonselected lung adenocarcinoma cases in East Asian populations [24], and an approximately 60% response rate was identified when they were treated with an EGFR-TKI [5,6,7,25,26,27]. On the other hand, only an approximately 5% EGFR mutation rate was detected in lung squamous cell carcinoma [28,29]. Furthermore, the median progression-free survival among patients with lung squamous cell carcinoma who showed a partial response to EGFR-TKIs seemed to be shorter than that commonly observed with lung adenocarcinoma (4-5 vs. 9-10 months) [30].…”
Section: Discussionmentioning
confidence: 99%